Tanggung Jawab Sosial Perusahaan PT Asia Forestama Raya di Kota Pekanbaru dan Penegakan Hukumnya - Utama, Andrew Shandy; Rizana, Rizana; Putra, Tri Anggara (Universitas Muhammadiyah Sumatera Barat, 2019)
Companies that carry out their business activities in the field of natural resources and / or fields related to natural resources must carry out corporate social responsibility. The field of corporate social responsibility can be carried out in the fields of education, health, infrastructure, sports and arts, social and religious arts, environmental preservation, populist economic endeavors, empowerment of indigenous peoples, and other fields of work that significantly impact the quality of the community. Based on the results of observations made in the Limbungan Village of Pekanbaru City, it is known that the corporate social responsibility program of PT Asia Forestama Raya was felt by the community. How is the implementation of corporate social responsibility of PT Asia Forestama Raya towards the community? How is law enforcement towards the implementation of corporate social responsibility of PT Asia Forestama Raya based on Riau Provincial Regulation Number 6 of 2012? The method used in this research is socio-legal research. The results of this research that PT Asia Forestama Raya actually implemented a corporate social responsibility program to the community of Limbungan Village, but it is not routinely carried out every year and does not cover all existing work fields. The obstacle is because the company's financial condition is currently in an unstable condition, so the budgeted corporate social responsibility funds are limited. Based on Article 32 of Riau Provincial Regulation Number 6 of 2012 it is affirmed that if PT Asia Forestama Raya does not carry out corporate social responsibility to the public, then the company will be subject to administrative sanctions by the Government of Pekanbaru City in the form of written warnings, restrictions on business activities, suspension of business activities , to revoke business activities.